Пуговицы из раковин моллюсков у аланского населения салтово-маяцкой культуры (по материалам катакомбных могильников бассейна Северского Донца) - Аксёнов, В.С. (Хазарский альманах, 2015)
В катакомбных захоронениях аланского населения салтово-маяцкой культуры достаточно часто встречаются так называемые пряжки-пуговицы из раковины моллюсков. При этом, согласно материалам дореволюционных раскопок, катакомбный могильник у с. Верхний Салтов образует вместе с Ютановским катакомбным могильником один кластер, для которого характерен самый низкий процент пуговиц или вообще отсутствие пуговиц, сделанных из раковины. The paper considers the buttons (disks) from the mollusk shells, which originate from 53 catacomb burial of the Verhne-Saltovskogo (45 burials), Staro-Saltovskogo (6 burials) and Rubezhansky (2 burials) and are stored in the Kharkov Historical Museum (91 examples). Materials of excavations show that the disks are found in the graves of children of both sexes, adolescent girls and young women of childbearing age. Such products are not typical for burials of adult men and older women. At human skeleton is 1–2 disks, and only in rare cases their number reaches three (cat. № 30 ВСМ-I, № 111 ВСМ-IV). Discs from the shell are placed in the area of the head, thorax (neck, shoulder) and belt of buried people, i.e. in the area of the upper part of the human body – in places associated with life and proper (head, chest), and the reproductive functions of people (belt). In semantic plane, we are inclined to believe that these buttons are a symbol of the Great Goddess, the foremother of all living things – the daughter of the lord of the water kingdom Dzerassu. Presence in the suits of children, girls of marriageable age, brides and women of childbearing age of buttons from mollusk shells (symbol of the Great Goddess) on the other – serves as a marker of age of the individual and his social status in the society.